Foreign aid and the failure of state building in Haiti under the Duvaliers, Aristide, Préval, and Martelly - Terry F. Buss (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
After receiving at least US20 billion in aid for reconstruction and development over the past 60 years, Haiti has been and remains a fragile state, one of the worse globally. The reasons for aid failure are legion but mostly relate to highly dysfunctional Haitian regimes, sometimes destructive US foreign policy and aid policy, and ongoing issues about how to deliver aid, all in the context of devastating natural disasters. The over-riding cause of aid failure has been the social, cultural and historical context which has led to domination by economic and political elites who have little interest in advancing Haiti, and who are totally self-interested - Haiti's fatal flaw. Donors can go far to improve aid effectiveness, but Haiti will languish until its leaders and people find common ground and compromise in managing their country.
Keywords: F35; 330; aid effectiveness; fragile states; foreign policy; donors